Do Not Read Beyond This Page: Postmodernism For Children - A stylistic examination of postmodern and metafictive strategies in children’s middle grade fiction - Wydrzynska, Ela (2023)
This thesis offers an extensive stylistic analysis of postmodern and metafictive devices in contemporary middle grade fiction (for readers aged approximately 8-12 years). Although terms like postmodernism and metafiction are often deemed culturally ‘highbrow’ or ‘avant-garde’, such strategies are rife in children’s literature to the point at which they can now be considered mainstream. This is evidenced through the examination of three best-selling children’s authors: recent UK Children’s Laureate Cressida Cowell, ‘celebrity author’ Tom Fletcher, and experimental writer Pseudonymous Bosch. In addition to their commercial success with the target readership, all three of these authors deploy a plethora of sophisticated postmodern and metafictive strategies in their books, creating complex narrative structures that rival the most acclaimed canonical literature and push the limits of existing narratological terminology.